Factors that influence bond markets development in Ghana - Alhassan Musah; Bernard Badu-Acquah; Eunice Adjei (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2019)
The various financial crises all over the globe underscore the need for economies to have vibrant bond markets to augment their financial portfolios. Among other benefits, this will enable them to support rapid and sustained infrastructural development, which in turn will lead to swift economic growth. The small size of the Ghanaian bond market, the accompanying huge infrastructural challenges, the overdependence on external debt and Deposit Money Banks (DMBs), the lopsided empirical evidence, which is concentrated on western and Asian economies coupled with mixed findings in related studies call for the need to examine the factors that promote the country‘s bond market development. This study therefore examines the influence of bond market determinants on the development of the bond market in Ghana. Data was collected from secondary sources covering a period from 1980 to 2015. The Vector Error Correction Model (VECM) is employed as technique of data analysis. The Augmented Dickey-Fuller (ADF) stationarity test, the Johansen Co-integration test and other tests are carried out to ensure the robustness of the results. The findings of the study reveal that bank size, external debt, money supply and size of the economy are significant determinants of corporate bond market development in Ghana. Also, level of economic development, budget deficit and bank size are significant determinants of government bond market size in Ghana. However, bank size, money supply and external debt are seen to be the most important and significant drivers of total bond market size in Ghana